Functional cooperation of mitochondrial protein import receptors in yeast. - Ramage, L (1993)
We have identified a 20 kDa yeast mitochondrial outer membrane protein (termed MAS20) which appears to function as a protein import receptor. We cloned, sequenced and physically mapped the MAS20 gene and found that the protein is homologous to the MOM19 import receptor from Neurospora crassa. MAS20 and MOM19 contain the sequence motif F-X-K-A-L-X-V/L, which is repeated several times with minor variations in the MAS70/MOM72 receptors. To determine how MAS20 functions together with the previously identified yeast receptor MAS70, we constructed yeast mutants lacking either one or both of the receptors. Deletion of either receptor alone had little or no effect on fermentative growth and only partially inhibited mitochondrial protein import in vivo. Deletion of both receptors was lethal. Deleting only MAS70 did not affect respiration; deleting only MAS20 caused loss of respiration, but respiration could be restored by overexpressing MAS70. Import of the F1-ATPase beta-subunit into isolated mitochondria was only partly inhibited by IgGs against either MAS20 or MAS70, but both IgGs inhibited import completely. We conclude that the two receptors have overlapping specificities for mitochondrial precursor proteins and that neither receptor is by itself essential.